Kajian Perubahan Luas Lahan Mangrove Di Desa Bedono Kecamatan Sayung Kabupaten Demak Menggunakan Citra Satelit Ikonos Tahun 2004 Dan 2009 - Chafid, Muhammad Abdul; Pribadi, Rudhi; Suryo, Agus Anugroho Dwi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangroves have an important role in coastal areas that provide great functionality and benefits. Nowadays, the quality and quantity of mangrove management is declining because the management is unbalanced, such as a good land for mangrove growth were used for the development of aquaculture, settlement, and others. So, it is necessary for the proper management for the utilization of mangrove areas can be done optimally and sustainably. The management can be done through monitoring the condition of the mangrove, one of them by using remote sensing technology via satellite. The purpose of this research is to know the changes of wide in mangrove land in the coastal area in Bedono village, District Sayung, Demak district from 2004 to 2009. The method which is used in this research is descriptive method. It is fact-finding method with appropriate interpretation. For the field survey uses squared sampling method, it makes the plot measuring 10 m x 10 m for the tree category in which there are 5 m x 5 m subplot for sapling category and 1 m x 1 m for seedling category. The results show that the land accretion mangrove area in the Bedono Village of years 2004 - 2009, from 22.41 ha in 2004 to 43.03 ha in 2009. Density of the dense mangroves suffered extensive increment of 5.06 ha in 2004 to 27.06 ha in 2009, the density of the moderate mangrove area is suffered extensive accretion of 2.41 ha in 2004 to 8.89 ha in 2009, while the density of rare mangrove area has decreased from 14.94 ha in 2004 to 7.08 ha in 2009. The Composition of mangrove vegetation is found in the coastal in the Bedono Village, Sayung District consists of three species, namely Avicennia Marina, Rhizophora Mucronata and Rhizophora Stylosa. The mangrove dominance of tree category is occupied by Avicennia Marina, while the category of sapling and seedling mangroves is dominated by Rhizophora Mucronata.